Answer:
Explanation:
15
It looks like the 4th one is the one you want to investigate. There are two ways you could do it.
- You could remove the brackets
- You could substitute as in y^2 - 5y - 8 ie y = x^2 - 4.
I think the second way is easier to do. You will wind up with a quartic (x^4) the first way.
let y = (x^2 - 4)
Therefore z = y^2 - 5y - 6
This factors into
z = (y - 6)(y + 1)
Now put (x^2 - 4) in for y
z = (x^2 - 4 - 6)(x^2 - 4 + 1)
z = (x^2 - 10)(x^2 - 3)
So it looks like I either made the wrong guess, or I made a mistake.
Let's try the first one
Let y =x + 2
y^2+2y -8
=(y +4)(y - 2)
=(x+2 + 4)(x + 2 - 2)
=(x+ 6)(x)
Looks like the first one is the answer.